Educaplay Froggy Jumps: Improving Cognitive Outcomes in Three-Variable Linear Equation Systems - Isaac Akbar Alfahquari Harisma Putra; Suwarno Suwarno; Hestu Wilujeng (Indonesian Journal of Mathematics and Natural Science Education, 2025)
Educaplay Froggy Jumps media is a solution to students' low daily test scores and is important to the teaching and learning process, making students more enthusiastic and active learners. It also significantly influences the learning process, affecting students' cognitive learning outcomes. The purpose of this study was to determine the effect of using Educaplay Froggy Jumps media on students' cognitive learning outcomes on the Three Variable Linear Equation System (SPLTV) material for class X at SMKN 3 Jember. This study used a quantitative approach with a Post-test Only Control Group Design. The sample consisted of class ten’s Tata Busana 1 (an experimental group) and class ten’s Tata Busana 2 (a control group), selected purposively. The p-value (2-tailed) for the hypothesis test was 0.040. Based on the decision-making criteria, because the sig value (2-tailed) <0.05, then H0 is rejected and Ha is accepted, so it can be concluded that there is a significant difference between the learning outcomes of the experimental class and the control class after the application of learning media in the form of educaplay froggy jumps media. This shows that the use of Eduplay Froggy Jumps media influences the cognitive learning outcomes of class X students at SMKN 3 Jember.